Maṣādiru Tamwīlil Ta’līmi fī al-Madrasati al-Islāmīyati min Manẓūri Niẓami Tamwili at-Ta’limi fī Indūnisiyā - Affan, Mohammad; Ulien Nuha, Zaki (Jurnal Al-Fawa'id : Jurnal Agama dan Bahasa, 2024)
Education has a very important role in promoting the civilization of the nation. A good education can encourage the creation of a good, creative and productive society so that it can finally achieve the goals of the state. Through this Indonesian national education system, the government must be able to ensure the equitable distribution of educational opportunities, as well as the importance and efficiency of education management to meet challenges in line with the changing demands of local, national and global life. The budget allocation system for education in Indonesia is strongly influenced by government policies. The researcher used the library research method by collecting information and data with the help of various materials found in the library such as reference books, similar previous research results, articles, notes and various journals related to the problem to be solved. Research activities are carried out by collecting information and data with the help of various materials in the library such as reference books, similar previous research results, articles, notes and various journals related to the problem to be solved. The research concluded that the financing of education in Indonesia through seven sources: Sources of funding from the central government from Law No. 20 of 2003 on the national education system, Article 49 "Education funds other than education salaries and official education costs are allocated at a minimum of 20% of the state budget and a minimum of 20% of the local revenue budget called the Public Allocation Fund and partially added with the Special Allocation Fund, local governments, parents of students, adoptive parents, community groups, students themselves and sources of institutions or associations.